2020
DOI: 10.1038/s41598-020-65839-8
|View full text |Cite
|
Sign up to set email alerts
|

HDO production from [2H7]glucose Quantitatively Identifies Warburg Metabolism

Abstract: Increased glucose uptake and aerobic glycolysis are striking features of many cancers. These features have led to many techniques for screening and diagnosis, but many are expensive, less feasible or have harmful side-effects. Here, we report a sensitive 1 H/ 2 H nMR method to measure the kinetics of lactate isotopomer and HDO production using a deuterated tracer. To test this hypothesis, HUH-7 hepatocellular carcinoma and AML12 normal hepatocytes were incubated with [ 2 H 7 ]glucose. 1 H/ 2 H nMR data were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 57 publications
1
26
0
Order By: Relevance
“…Previous work suggests that it could account for a maximum of 8% of the HDO generation when using [6,6‐ 2 H 2 ]glucose, 10 indicating that its contribution in this case should be very small in relative terms. In our recent work in Huh‐7 cancer cells incubated with [ 2 H 7 ]glucose, we observed that unlabeled lactate increased with time, suggesting significant deuterium loss during glycolysis 11 . The stoichiometry of the metabolism of the deuterated tracer is such that the number of HDO molecules produced by glycolysis versus glx and lactate 2 H enrichment varies depending upon whether the glycolytically derived pyruvate methyl group is produced from either the C1 or C6 position of glucose (Figure 5).…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations
“…Previous work suggests that it could account for a maximum of 8% of the HDO generation when using [6,6‐ 2 H 2 ]glucose, 10 indicating that its contribution in this case should be very small in relative terms. In our recent work in Huh‐7 cancer cells incubated with [ 2 H 7 ]glucose, we observed that unlabeled lactate increased with time, suggesting significant deuterium loss during glycolysis 11 . The stoichiometry of the metabolism of the deuterated tracer is such that the number of HDO molecules produced by glycolysis versus glx and lactate 2 H enrichment varies depending upon whether the glycolytically derived pyruvate methyl group is produced from either the C1 or C6 position of glucose (Figure 5).…”
Section: Discussionmentioning
confidence: 83%
“…In our recent work in Huh-7 cancer cells incubated with [ 2 H 7 ]glucose, we observed that unlabeled lactate increased with time, suggesting significant deuterium loss during glycolysis. 11 The stoichiometry of the metabolism of the deuterated tracer is such that the number of HDO molecules produced by glycolysis versus glx and lactate 2 H enrichment varies depending upon whether the glycolytically derived pyruvate methyl group is produced from either the C1 or C6 position of glucose ( Figure 5). Multiple reactions, including equilibration at M6P, alanine, or glucose, HDO, glx, and lactate was calculated using the fitted areas for the 2 H-MRS data from rat brain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 4 also hints at statistically significant differences between the rates of 2 H‐water generation in kidneys and in tumors; in fact, for both the PDAC models, 2 H‐water images were also found to highlight the tumors over the remaining organs in the abdomen. Water has been reported as an end product of glycolysis and of other metabolic processes including the pentose phosphate and the TCA pathways 39,40 ; some of these pathways may also be stimulated in cancer cells, 41 and the DMI data could be reflecting this. However, neither the experimental kinetic curves for water nor their statistical modeling led to the kind of clearer trends evidenced by the glucose and lactate clearance rates, and hence the detailed message conveyed by the 2 H‐water production in these experiments remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%